Novel egg-carton-shaped paraffin microsheet for high-density latent heat storage - Kim, Somin; Jo, Byeongnam (Solar Energy Materials and Solar Cells, 2024)
Thermal energy storage (TES) systems are significant to solve inevitable intermittency and curtailment issues of clean renewable energy sources. Thus, the high-density and high-efficient TES technologies are required to achieve carbon neutrality. This study aims to synthesize an egg-carton-shaped paraffin microsheet for high-density latent heat storage. Poly(methyl methacrylate) (PMMA) microparticles (3 μm in diameter) are homogeneously placed onto a silicon wafer (10 × 10 mm2) via Langmuir–Blodgett technique. The PMMA monolayer on the silicon wafer is then dipped in a colloidal silica sol and dried to form the bottom structure of the egg-carton. Paraffin, a phase change material with a large melting enthalpy, is injected into the void space of the egg-carton produced by the decomposition of the PMMA particles. Finally, the upper silica shell covers the egg-carton structure with spherical paraffin to ultimately obtain an approximately 3.4-μm-thick microsheet for latent heat storage. The thermal performance of the paraffin microsheets is evaluated using differential scanning calorimetry. The encapsulation ratio, defined as the mass ratio of the paraffin to the microsheet, is calculated to be approximately 80.2%. This novel paraffin microsheet enables an increase in the TES capacity and ultimately overcomes poor heat transfer in paraffin owing to its low thermal conductivity.
Keywords: Dip coating; Intermittency; Langmuir Blodgett techniques; Latent heat storage; Microsheet; Poly(methyl methacrylate); Poly-methyl methacrylates; Renewable energy source; Thermal energy storage; Thermal energy storage systems; Dip-coating; Langmuir–blodgett technique; Latent heat storage; Microsheet; Phase change material